RETENSI DAN PENETRASI EKSTRAK BIJI PINANG (Areca catechu L.) SEBAGAI BAHAN PENGAWET NABATI KAYU MAHANG (Macaranga gigantea Mull. Arg.) - Hanifah Ikhsani; Rudianda Sulaeman; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to determine the concentration of preservative use of betel nut Areca catechu L. extract is best based preserpative retention and penetration of the highest in the stem (tip, middle and butt) mahang wood. The research used method completely randomized design (CRD) arranged factorially with 2 (two) factors. The first factor is the concentration of the curing agent (B) consist of three 3 (three) level, namely B1 (20% concentration), B2 (25% concentration) and B3 (30% concentration). The second factor is the wooden rod (C) consist of 3 (three) level, namely C1 (butt), C2 (middle of timber) and C3 (wood tip). Concentration of plant extract preservative us Areca catechu L. is best based preservative highest retention was 30% at tip (18,33 kg/m3), middle (16,03 kg/m3) and butt (15,55 kg/m3), whereas the concentration of plant extract preservative us betel nut Areca catechu L. is best based preservative highest penetration was 30% at tip (63,76%), middle (53,93%) and butt (50,06%) mahang wood.   Keywords: Macaranga gigantea, Areca catechu, wood preservative.